Jadranska orijentacija Zagreba u prošlosti - Kolar-Dimitrijević, Mira (Promet - Traffic&Transportation)
Natural barriers on the route between the seaside and North Croatia have to a degree always hindered traffic and transport of people and goods. This has readily been accepted by different opponents of unified Croatian national territory, advocating the optimal aspect of linkage of the Balkan region on the East- West horizontal rather than on the North-South vertical, so that such ideas have been promoted and materialized on many occasions in the past.